Multiple cascode flipped active inductor‐based tunable bandpass filter for fully integrated RF front‐end. Issue 1 (13th January 2020) - Nediyara Suresh, Lakshmi; Manickam, Bhaskar
Abstract : A multiple cascode flipped active inductor (MCASFAI) is proposed to determine the degrees of freedom in cascode flipped active inductor (CASFAI). The inductance value of CASFAI is dependent on negative transconductor in gyrator network. This finding is in contrast to the finding that has been reported in the literature, on the degrees of freedom in CASFAI. As the transconductance of negative transconductor increases, inductance decreases, and quality factor increases. The MCASFAI proposed in this study is designed to enhance both inductance and quality factor of CASFAIs. Analytical modelling is done to determine the design parameters that affect inductance and quality factor in CASFAI. Verification is done using Cadence Virtuoso in 180 nm process. Bandpass filter based on the proposed MCASFAI is designed to operate at 2.45 GHz centre frequency with a bandwidth of 80 MHz. The designed filter attains a dynamic range of 162 dB‐Hz and figure of merit of 153 dB‐HZ/mW, which is comparable to the bandpass filter designs reported in the literature.